2017
DOI: 10.1631/jzus.b1600205
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA-718, a new regulator of EGR3, in regulation of malignant phenotype of HCC cells

Abstract: Abstract:Objective: Hepatocellular carcinoma (HCC) is still one of the most common death-related malignancies worldwide. Because the way onset and progression are hidden most, HCC diagnoses are made at an advanced stage, when they are unsuitable for surgical resection. MicroRNAs are a class of small non-coding RNAs, participating in many aspects of cancers. In this study, we tried to establish the role of microRNA-718 (miR-718) in the malignant phenotype of HCC cells and its possible role in HCC diagnosis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…We found an increase in EGR3 protein expression in migrating tumour cells in the periphery, suggesting that EGR3 plays a role in tumour cell migration, thereby indirectly causing accelerated tumour progression, which leads to poor patient outcome. Supporting this hypothesis, a decline of EGR3 expression has been shown to decrease motility of non-small cell lung cancer cells 39 , while EGR3 has been associated with migration and invasion in hepatocellular 40,41 and breast carcinomas 21 .…”
Section: Discussionmentioning
confidence: 88%
“…We found an increase in EGR3 protein expression in migrating tumour cells in the periphery, suggesting that EGR3 plays a role in tumour cell migration, thereby indirectly causing accelerated tumour progression, which leads to poor patient outcome. Supporting this hypothesis, a decline of EGR3 expression has been shown to decrease motility of non-small cell lung cancer cells 39 , while EGR3 has been associated with migration and invasion in hepatocellular 40,41 and breast carcinomas 21 .…”
Section: Discussionmentioning
confidence: 88%
“…As previously reported, EGR1 plays multiple tumor suppressor roles in breast cancer, in which its expression is often lost ( Crawford et al, 2019 ); EGR2 is a growth inhibitor when upregulated in tumor cells ( Salotti et al, 2015 ), exogenous expression of EGR2 can also suppress the growth of tumor cells ( Unoki and Nakamura, 2003 ), but its role in breast cancer is rarely reported; downregulation of EGR3 can promote the migration and invasion of hepatocellular carcinoma (HCC) ( Wangdong et al, 2017 ), high expression level of EGR3 was discovered in prostate cancer samples ( Pio et al, 2013 ), but its role in breast cancer is also rarely reported. Few researches reported EGR4 in malignant tumors; only some articles reported that EGR4 might promote NSCLC ( He et al, 2019 ), small cell lung cancer (SCLC) ( Matsuo et al, 2014 ), and cholangiocarcinoma (CHOL) to develop ( Gong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can regulate numerous genes at the post-transcriptional level, and the aberrant expression of miRNAs is closely associated with the development of neoplasms in humans (36). Recently, a substantial number of cancer-specific miRNAs have been identified as tumor biomarkers in various types of cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%